Personal reasons for withdrawal from team sports and the influence of significant others among youth athletes - Rottensteiner, C.; Laakso, L.; Pihlaja, T.; Konttinen, N. (International Journal of Sports Science and Coaching, 2013)
The aim of this study was to identify the main reasons for withdrawal from team sports and to examine the influence of significant others (i.e., coaches, parents, peers, and siblings) in the decision making concerning withdrawal from youth sports. An attempt was also made to compare withdrawal components and the influence of significant others in terms of gender, level of competition and years of involvement in youth sports. The participants in this study were young football (American soccer) (n=397), ice hockey (n=88) and basketball (n=50) players who had terminated their participation in their sports. Principal component analysis was used to reduce the number of withdrawal items and identify principal withdrawal components. The results indicated that having other things to do and a decline in excitement were the most important reasons for withdrawal. Coaches and teammates appeared to be the two main groups of significant others who influenced young player's decision making related to their withdrawal. Statistically significant differences in withdrawal components related to ability and social issues were found between gender and years of involvement. The present findings highlight the factors that are related to the incidence of withdrawal, and at the same time, underline the role of significant others within the contexts of sport participation. Recommendations and practical implications for coaches and policy makers to reduce the withdrawal rate among young athletes are provided.